The use of routine data sources to identify risk factors for overweight and obesity at 6 years of age. An Italian study in 8621 children born in 2010-2011-2012 - Riccardo Pertile; Anna Schönsberg; Claudio Maffeis; William Mantovani (Italian Journal of Pediatrics)
Abstract Background the growing prevalence of paediatric obesity represents a problem of considerable urgency, with potential repercussions on the health of the individual in both the short and long term. The aim of this study was to identify risk factors associated with the development of obesity and overweight in children at age six years. Methods this longitudinal observational study included 8,621 out of 15,903 children born in Trentino region between 1st January 2010 and 31st December 2012 and still alive and resident in the same region at the age of 6, with a coverage of 54.2%. Data from the Italian Birth Attendance Certificate database and the Health Surveillance Forms filled out by paediatricians during the 12-month and 6-year check-ups were collected. Two multivariable models on the estimation of Prevalence Ratios (PRs) were conducted to identify independent predictors of the probability of presenting obesity or overweight at 6 years of life, separately. Results Using the threshold values of the International Obesity Task Force as a reference, the prevalence of overweight and obesity at 6 years of age was 15.7% and 6.7%, respectively. Among prenatal factors, pre-pregnancy maternal body mass index (BMI) and the presence of gestational diabetes were found to positively influence the risk of obesity at 6 years. Regarding postnatal factors, birth weight, being the firstborn, male gender, as well as a BMI exceeding 2 standard deviations at 12th month of life were identified as risk factors for obesity. South American ethnicity, low maternal education, smoking during pregnancy and a smoking habit by at least one parent were also identified as risk factors for obesity. Similar results were obtained for the risk of overweight. Conclusions the record linkage of routine paediatric healthcare data has made it possible to identify the updated prevalence of obesity and overweight in 6-year-old children and to anticipate the timing of interception of these children (pre-school age).